Urgensi Pengesahan Rancangan Undang-Undang Penghapusan Kekerasan Seksual terhadap Pekerja Perempuan di Sektor Pariwisata - Monica, Anindwitya Rizqi; Risfiana, Annisa; Cloudia Rohman, Holy Melinda (Jurnal Suara Hukum, 2022)
Tourism is Indonesia's mainstay sector which is growing rapidly and supports the involvement of women in it. However, this condition tends to be contradictory when considering the lack of security felt by women workers in this sector, given the many acts of discrimination, subordination, and sexual violence in the work environment--especially because of the complex dimensions of power relations that affect it. Then, the Bill on the Elimination of Sexual Violence (RUU-PKS) became a major goal to realize a gender-friendly tourism sector and provide a safe space from sexual violence. This study aims to examine the acts of sexual violence experienced by women in the tourism sector, and its relation to the urgency of the ratification of the RUU-PKS--as a comprehensive regulation in handling cases of sexual violence--by using field data collection techniques, namely interviews and literature studies. In addition, this qualitative research method intends to support the acceleration of the ratification of the RUU-PKS which is considered to have inclusive substance, starting from the categorization of sexual violence, handling, to efforts to recover women survivors.